Woven Coronary Artery Disease Successfully Managed with Percutaneous Coronary Intervention: A New Case Report - Yakup Alsancak; Burak Sezenoz; Sedat Turkoglu; Adnan Abacı (Case Reports in Cardiology)
Woven coronary artery is relatively rare and can be complicated in both acute and chronic phases. A few case reports have been published until now. Herein we report a case with right woven coronary artery managed with drug-eluted stent implantation without complication.